Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode WASPAS - Raheliya Br Ginting; Dewi Yohana Br Ginting; Dito Putro Utomo (Bulletin of Information Technology (BIT), 2024)
Human resources or employees in a company organization are very important to support the progress and quality of the company in achieving its goals. Having employees with good performance in a company does not just come from the employees themselves but there must also be a role from the company. Providing rewards to employees is one factor that can be used as a basis for providing motivation to employees. Performance appraisal is a process of measuring the results of work provided by employees, where this assessment will later provide results on who the best employees have the best performance to get rewards from the company. The problem that often occurs is that selecting the best employees or evaluating employee performance is based on subjective factors, which of course is detrimental to other employees and also has an impact on the company. Decision Support System (DSS) is a process that is part of the information system. Where the decision support system will assist in the process of completing semi-structured data processing. The Weight Aggregate Sum Product Assessment (WASPAS) method is a method that can be used in making decisions that have many attributes or criteria or is also known as MCDM (Multi Criteria Decision Making). The method used in this research is the WASPAS method which can provide the best alternative results, namely alternative A6 with the name "Tian" with a Qi value = 0.9815 which was selected as the best employee